Impact of Running Wheel’s Vertical Stiffness on Curve Negotiation Performance of Straddle-type Monorail Vehicle - DU Zi-xue; ZUO Chang-yong (机车电传动)
The straddle-type monorail vehicle was mainly guiding by the steering wheel when it throughing the curve. Therefore, the size of steering wheel’s radial force was an important index to evaluate the curve negotiation performance of monorail vehicle. Simulation model of monorail vehicle based on the multi-body dynamics simulation analysis software-ADAMS was established. Under the condition of orbit radius and super-high no changing and vehicle running with constant speed, radial force characters of steering wheel and its impact on curve negotiation performance of vehicle were analyzed by changing the size of the running wheel’s vertical stiffness. The simulation and analysis showed that running wheel’s vertical stiffness had great influence to vehicle curve negotiation performance.